Information support for agricultural policy formulation in Africa: role of international organisations - Heydon, D. (Technical Centre for Agricultural and Rural Cooperation, 1999)
The objectives of this study were to review the policies and activities of 13 international organisations, to assess their efforts to improve the use of information in agricultural policy-making in Africa ...